146k views
3 votes
-4(3 - 2x) + 2x = 2x4

User Phentnil
by
5.1k points

1 Answer

3 votes

Answer:

No solution

Explanation:

Knowing the equation -4(3 - 2x) + 2x = 2x(4), we can tell that we need to solve for x.

First, we can distribute out multiplication on both sides:

-4(3 + (-2x)) + 2x = 2x(4)

(-4)(3) + (-4)(-2x) = 2x(4)

-12 + 8x = 8x

Second, we can subtract 8x from both sides:

-12 + 8x = 8x

-12 = 8x - 8x

-12 = 0

This shows that there are no solutions to this equation for x.

User Gaelle
by
4.7k points